Comparative genetic analysis of quantitative traits in sunflower - Bert, P. -F; Dechamp-Guillaume, G; Serre, F; Jouan, I; de Labrouhe, D. Tourvieille; Nicolas, P; Vear, F (Theoretical and applied genetics, 2004)
One hundred and fifty F sub(2)-F sub(3) families from a cross between two inbred sunflower lines FU and PAZ2 were used to map quantitative trait loci (QTL) for resistance to white rot (Sclerotinia sclerotiorum) attacks of terminal buds and capitula, and black stem (Phoma macdonaldii). A genetic linkage map of 18 linkage groups with 216 molecular markers spanning 1,937 cM was constructed. Disease resistances were measured in field experiments for S. sclerotiorum and under controlled conditions for P. macdonaldii. For resistance to S. sclerotiorum terminal bud attack, seven QTL were identified, each explaining less than 10% of phenotypic variance. For capitulum attack by this parasite, there were four QTL (each explaining up to 20% of variation) and for P. macdonaldii resistance, four QTL were identified, each having effects of up to 16%. The S. sclerotiorum capitulum resistance QTL were compared with those reported previously and it was concluded that resistance to this disease is governed by a considerable number of QTL, located on almost all the sunflower linkage groups.